PENYUSUNAN PROGRAM BANTU BERBASIS MEH DAN METODE PSEUDO-MODAL UNTUK ANALISIS DINAMIK SISTEM POROS-ROTOR - Suweca, I Wiratmaja; Santika, I Komang Jaya (Mesin, 2001)
This paper presents a strategy in analyzing shaft-rotor dynamics system based on finite element and pseudo-modal methods by using MATLABÂ® programming language. The validation of computer program developed in this study is carried out by comparing the results with those obtained in the reference [1]. The computer program then is used to analyze the dynamic behavior of the electric generator 1FC 1801 produced by PT PINDAD (Persero). The validations of the computer programâs results with those obtained in reference [1] have shown a very good agreement. The application of the computer program in analyzing the dynamic behavior of electric generator type 1FC 1801 has shown that the rotor dynamic system has no critical speed in the range of its operational speed.